Comparison of wet-only and bulk deposition at Chiang Mai (Thailand) based on rainwater chemical composition - Somporn Chantara (2018)
The chemical composition of 122 rainwater samples collected daily from bulk and wet-only collectors in a sub-urban area of Chiang Mai (Thailand) during August 2005-July 2006 has been analyzed and compared to assess usability of a cheaper and less complex bulk collector over a sophisticated wet-only collector. Statistical analysis was performed on log-transformed daily rain amount and depositions of major ions for each collector type. The analysis of variance (ANOVA) test revealed that the amount of rainfall collected from a rain gauge, bulk collector and wet-only collector showed no significant difference (∝=0.05). The volume weight mean electro-conductivity (EC) values of bulk and wet-only samples were 0.69 and 0.65 mS/m, respectively. The average pH of the samples from both types of collectors was 5.5. Scatter plots between log-transformed depositions of specific ions obtained from bulk and wet-only samples showed high correlation (r>0.91). Means of log-transformed bulk deposition were 14% (Na+and K+), 13% (Mg2+), 7% (Ca2+), 4% (NO3-), 3% (SO42-and Cl-) and 2% (NH4+) higher than that of wet-only deposition. However, multivariate analysis of variance (MANOVA) revealed that ion depositions obtained from bulk and wet-only collectors were not significantly different (∝=0.05). Therefore, it was concluded that a bulk collector can be used instead of a wet-only collector in a sub-urban area. © 2008 Elsevier Ltd. All rights reserved.